Fundamentals of tooth preparations for cast metal and porcelain restorations - Shillingburg, Herbert T.; Shillingburg, Herbert T.; Brackett, Susan E. (Chicago : Quintessence Publishing Co, Inc., 2019)
Proper tooth preparation is critical for pulpal vitality, periodontal health, esthetics, strength, occlusal stability, and life span of the restoration. In 17 chapters, this book details theory and application of tooth preparation. Both beginning and advanced students will gain insight into tooth-preparation design.
Fundamentals of tooth preparations for cast metal and porcelain restorations -- Contributors -- Dedication -- Contents -- Acknowledgments -- Introduction -- References -- Chapter 1: Biomechanical Principles of Preparations -- Chapter 2: Finish Lines and the Periodontium -- Chapter 3: Instrumentation -- Chapter 4: Full Veneer Crowns -- Chapter 5: Maxillary Posterior Three-Quarter Crowns -- Chapter 6: Mandibular Posterior Three-Quarter Crowns -- Chapter 7: Anterior Three-Quarter Crowns -- Chapter 8: Pin-Modified Three-Quarter Crowns -- Chapter 9: Seven-Eighths Crowns -- Chapter 10: Proximal Half-Crowns -- Chapter 11: Inlays -- Chapter 12: MOD Onlays -- Chapter 13: Anterior Porcelain-Fused-to-Metal Crowns -- Chapter 14: Posterior Porcelain-Fused-To-Metal Crowns -- Chapter 15: All-Ceramic Crowns -- Chapter 16: Preparation Modifications for Damaged Teeth -- Chapter 17: Preparation Modifications for Special Situations -- References.
Includes bibliographical references and index.
Keywords: Dental Cavity Preparation -- methods; Dental Restoration, Permanen